ปัญหาสังคมที่เกิดจากการจ้างแรงงานต่างด้าวที่ตลาดสี่มุมเมือง จังหวัดปทุมธานี - สมพร พรทิพย์เสถียร (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The main purpose of this research was to study the social problems caused by employment of foreign workers by using six variables namely : sex , age , income, marital status, period of work, the working unit which consist of workers. The See-Moom-Muang Market in Pathumthani Province was chosen for this study. One hundred and ninety-nine employers were selected as the sample size. The data was analyzed by using questionnaire, documentary research, general observation, informal interview, in-depth interview. Analysis of data was conducted by using SPSS/PC program to calculate percentage, means and hypotheses testing by chi-square with the level of significance at 0.05. The hypotheses were as follows: 1.Male foreign workers will cause social problems higher than female foreign workers. 2. Young foreign workers will cause social problems higher than old foreign workers. 3. Low income foreign workers will cause social problems higher than high income foreign workers. 4. Single foreign workers will cause social problems higher than the married foreign workers. 5. Long working period foreign workers will cause social problems higher than short working period foreign workers. 6. Foreign workers who work in the working unit which consist of a lot of workers will cause social problems higher than foreign workers who work in the working unit which consist of less workers. The results of the research agreed with hypotheses numbers 1,2,3,5,6 and rejected hypothesis number 4.